FAKTOR – FAKTOR YANG MEMPENGARUHI RETURN ON ASSET (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2016) - Mega Anggun Pertiwi, 14.05.52.0284; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This study aims to examine current assets, total asset turnver, debt to equity ratio, sales growth and firm size on return on assets in manufacturing companies listed on the Indonesia Stock Exchange in the period 2013 - 2016. The population in this study were registered manufacturing companies on the Indonesian stock exchange. The sampling method uses purposive sampling with the study period of 2013 to 2016, the data processed is 220. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the current ratio has a positive influence on return on assets. Total asset turnover has a positive effect on return on assets. Debt to equity ratio negative affects return on assets. Sales growth has a positive effect on return on assets, and the firm size has a negative effect on return on assets. Keywords : current assets, total asset turnver, debt to equity ratio, sales growth, firm size and return on assets